Heroic Helping: The Effects of Priming Superhero Images on Prosociality - Van Tongeren, Daryl R.; Hibbard, Rachel; Edwards, Megan; Johnson, Evan; Diepholz, Kirstin; Newbound, Hanna; Shay, Andrew; Houpt, Russell; Cairo, Athena; Green, Jeffrey D. (Frontiers in Psychology, 2018)
Two experiments examined how exposure to superhero images influences both prosociality and meaning in life. In Experiment 1 (N = 246) exposed individuals to scenes with superhero images or neutral images. Individuals primed with superhero images reported greater helping intentions relative to the control group, which, in turn, were associated with increased meaning in life (indirect effect only; no direct effect). In Experiment 2 (N = 123), individuals exposed to a superhero poster helped an experimenter in a tedious task more than those exposed to a bicycle poster, though no differences were found for meaning in life. These results suggest that subtle activation of superhero stimuli increases prosocial intentions and behavior.